FDG-PET is not useful in early pancreatic cancer diagnosis - Strobel, Oliver; Büchler, Markus W. (Nature reviews. Gastroenterology & hepatology, 2013)
Better tools for early detection and accurate staging of pancreatic cancer are needed. The role of 18F-fluorodeoxyglucose (FDG)-PET in this setting is controversial. The results of a large retrospective study analyzing the value of FDG-PET in the diagnosis of pancreatic ductal adenocarcinoma are discussed here.